Mouth morphing using affine transformation / Mohd Asnawi Fadzial - Fadzial, Mohd Asnawi (2010)
Morphing is an image processing technique used for the metamorphosis from one image to another. Morphing is used in entertainment industry such as in movies, TV commercials and music videos. Morphing is also used in the gaming industry to add engaging animation to video games and computer games. Morphing is a powerful tool that can enhance many multimedia projects such as presentations, education, electronic book illustrations, and computer-based training. Morphing can be done by getting a sequence of intermediate images which when put together with the original images would represent the change from one image to the other. For this project, affine transformation technique was used to morph images. The implementation of the project shows that the affine transformation technique can morph mouth images.